Variation in internal polysaccharide synthesis among Streptococcus mutans strains. - Freedman, M L (1975)
Five strains, representative of Streptococcus mutans genetic group III antigenic group d, synthesized and degraded less intracellular polysaccharide (IPS) then 17 strains representative of other S. mutans groups. The strains that synthesize IPS degraded it rapidly. The production of acid in titratable amounts from endogenous IPS was usually complete within 1 h. IPS synthesis in S. mutans increased abruptly at culture glucose concentrations between 0.2 and 0.5% and was quantitated as both iodine-and glucose oxidase-positive material in cell hyrolysates. IPS degradation was measured by acid production in a pH-stat maintained at 7. The existence within group III d of a strain recently shown to be cariogenic in experimental animals suggest that IPS may not be a prerequisite for virulence in these cariogenic bacteria.